Neopomacentrus flavicauda: a replacement name for Neopomacentrus xanthurus Allen & Randall, 1981 (Perciformes: Pomacentridae), a secondary junior homonym of Dascyllus xanthurus Bleeker, 1853 - Fricke, Ronald; Allen, Gerald R. (Zootaxa, 2021)
N/A